Dissemination of Carbapenemases in Gram-negative Bacteria in Brazilian Hospitals: A Review - , Rafaela Linhares Ponte Rangel; , Izabelly Linhares Ponte Brito; , Amanda Barbosa Linhares; , Antonio Osmundo de Vascelos Neto; , Claudio Roberto Ferreira de Sousa; , Ana Kelvia Araújo Arcanjo; , Maria Gabriela Linhares Ponte; , Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2025)
Antimicrobial resistance in bacteria with carbapenemase activity is a growing public health problem of global proportions. This integrative review synthesizes data from 26 scientific articles published between 2020 and 2024 to analyze the dissemination and genetic diversity of carbapenemases in Brazil. Data were retrieved from the National Library of Medicine (PubMed) and the regional portal of the Virtual Health Library (BVS). The review highlights significant regional variability in carbapenemase prevalence, with the blaKPC gene being the most frequently identified resistance mechanism across multiple Brazilian states. The identification of novel trends, including the simultaneous presence of blaNDM and blaKPC genes in isolates of Proteus mirabilis and Serratia marcescens, in addition to the observation of blaNDM in Klebsiella aerogenes, highlights the intricate nature of antimicrobial resistance patterns. The state of Pernambuco is notable for reporting the first identification of blaVIM-2 in Acinetobacter baumannii and the blaOXA-23-like and blaOXA-143 genes. These findings emphasize the widespread cohabitation of resistance genes, with mobile genetic elements facilitating intra- and interspecies transfer among Gram-negative bacilli. Understanding this genetic diversity is crucial for developing targeted public health interventions. The study underscores the urgent need for enhanced genomic surveillance, robust infection prevention measures, and strengthened antimicrobial stewardship programs to address the growing threat of multidrug-resistant organisms in Brazil and mitigate their impact on global health.